(untitled) (Biological Sciences - PJSIR, 2022)
A furanyl analog of dehydro-L-ascorbic acid ill) was synthesized starting from .!2-glucose via its condensation with ethyl acetoacetate followed by periodate oxidation. Acyloin condensation of the obtained aldehyde a)with glyoxal in presence of potassium cyanide afforded the imide (1) with aqueous acetic acid gave (ID which when treated with aryl or acylhydrazines afforded the pyrazolin derivatives (2J.Q) whereas with Q-phenylencdi.unine gave a quinoxaline de- rivative (11). Acylation of (1) gave monoacyl derivatives (1), while With aryl and acylhydrazincs gave the correspond- ing hydrazones ). On the other hand, treatment of (1)with nitrous acid gave the title compound ill).Reaction of ill) with aryl or acylhydrazines gave the corresponding bis (hydrazones) (13,14), rearrangement of ill) gave the pyrazoline (12). Reaction of ill) with Q-phenylenediamine gave the quinoxaline derivative ill). Reaction of ill) with aryl or acylhydrazines gave monohydrazones (] 7.18).